2004
DOI: 10.1002/elan.200302861
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Effect of Li+ on the Voltammetric Properties of [PMo12O40]3−. Part 2: Comparative Studies on the Preferential Solvation in Acetonitrile+S and Acetone+S Mixtures

Abstract: , the presence of Li produced a two-electron wave at nearly the same potential as the first oneelectron wave in acetonitrile or acetone. The voltammetric behavior of [PMo 12 O 40 ] 3À in a binary mixture of acetonitrile and solvent S was compared with those in a mixture of acetone and S. When the donor number (DN) of S > 20, the first two-electron wave was converted into one-electron waves in such binary mixtures. The conversion occurred at lower mole fractions of S in an acetonitrile S mixture than in an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The effects of Li + and Na + on the voltammetric behavior of Keggin‐type POMs were investigated in various solvents with the help of 7 Li NMR, leading to the selective solvation of Li + in binary solvents. The Li‐coupled reduction processes of PMo 12 O 40 ] 3‐ was investigated in acetone to obtain protonation constants and Li association constants (Scheme S6) …”
Section: Simulationmentioning
confidence: 99%
“…The effects of Li + and Na + on the voltammetric behavior of Keggin‐type POMs were investigated in various solvents with the help of 7 Li NMR, leading to the selective solvation of Li + in binary solvents. The Li‐coupled reduction processes of PMo 12 O 40 ] 3‐ was investigated in acetone to obtain protonation constants and Li association constants (Scheme S6) …”
Section: Simulationmentioning
confidence: 99%
“…It is well known that the redox potential of POMs depends on negative charges of POMs, the type of counter cations and the pH of the solution. [17][18][19][20][21][22][23] It is also known that the redox potentials of POMs are affected by anion solvation. 18,19,[24][25][26] Keita and Nadjo's group reported that the first one-electron reduction potentials of [SiW 12 O 40 ] 4−/5− and [P 2 W 18 O 62 ] 6−/7− were shifted to more positive potentials with increases in the Gutmann acceptor number 27 of the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Small cations, such as H + , Li + and Na + , were more strongly associated with the reduced forms of POMs than with the corresponding oxidised forms and caused changes in the redox potentials and/or number of transferred electrons. [20][21][22][23]31,32 Himeno's group reported that the solvation ability to small cations increased with an increase in the Lewis basicity (≈donor number) of solvents and that the solvation of cations caused weakening of the interaction between the small cations and POMs. 21,22 Thus, the redox potential changes for POM anions are rationalized in terms of the electron donor-acceptor concept of the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of water always is ubiquitous but often overlooked as a background environment in the water and organic solvent. In fact, the preferential solvation of water plays an important role in electrochemical behavior of solute , hydrogen evolution reaction , double layer capacitance , the process of electronic transfer . Exploring preferential solvation of water by electrochemical methods would provide new insights into the effect of water in the field of electrochemical research.…”
Section: Introductionmentioning
confidence: 99%